USE OF PEDAGOGICAL TECHNOLOGIES IN TEACHING STUDENTS TO NUMBER - Bozorov, Murot Nashvandovich (Fakultas Ilmu Pendidikan, Universitas Persatuan Guru Republik Indonesia Semarang, 2024)
Numbers need to be introduced to children from an early age, so teaching numbers in elementary school is something important to implement. The aim of this research is to describe the pedagogical technique (charkhpalak method) used by teachers in teaching numbers to students in elementary schools in Uzbekistan. This type of research is descriptive qualitative where the researcher describes the research objects encountered in the field. The data collection method used was observation where the researcher made observations of teaching and learning activities in elementary schools when the teacher used the Charkhpalak method to teach numbers. The research results show that the Charkhpalak method is able to make students easily understand the material being taught. The conclusion obtained from this research is that the Charkhpalak method needs to also be applied to other learning materials because this method provides several benefits for teachers.